PROBLEM OF MISTAKES IN DATABASES, PROCESSING AND INTERPRETATION OF OBSERVATIONS OF THE SUN. I. - Lozitska, N. I. (Одеські астрономічні публікації, 2016)
In databases of observations unnoticed mistakes and misprints could occur at any stage of observation, preparation and processing of databases. The current detection of errors is complicated by the fact that the works of observer, databases compiler and researcher were divided. Data acquisition from a spacecraft requires the greater amount of researchers than for ground-based observations. As a result, the probability of errors is increasing. Keeping track of the errors on each stage is very difficult, so we use of cross-comparison of data from different sources. We revealed some misprints in the typographic and digital results of sunspot group area measurements.